Reliable sideline ocular-motor assessment following exercise in healthy student athletes. Issue 12 (December 2019) - Sundaram, Vandana; Ding, Victoria Y.; Desai, Manisha; Lumba-Brown, Angela; Little, Jessica
Abstract: Objectives: To assess the reliability and effect of exercise on sideline dynamic visual performance measures of ocular-motor function using a portable visual assessment system ( EYE-SYNC ®). Design: Prospective cohort study. Methods: Healthy student athletes, ages 18–25 years, performed eye-tracking six times—three times consecutively prior to and after practice—using EYE-SYNC® goggles. Ocular-motor performance was assessed by calculating five gaze error outcomes between target position and actual gaze position to inform dynamic visual synchronization. We assessed reliability by calculating the intraclass correlation coefficient (ICC) for each outcome (we defined the standard deviation of tangential error (SDTE) as our primary outcome) and calculated differences in mean pre- and post-practice scores. Results: ICCs for the SDTE score were 0.86 (95% confidence interval, CI: 0.82–0.9) and 0.88 (0.84–0.91) at pre- and post-practice, respectively. 133 (89%) and 135 (90%) of 150 athletes had at least one measurement at pre- and post-practice, respectively. 117 (78%) and 122 (81%) athletes had more than one SDTE score at pre- and post-practice, respectively. The absolute mean (SD) differences between pre- and post-practice mean scores ranged from 0.02 (0.05) for horizontal gain to 0.1 (0.5) for SDTE. Conclusions: We observed high ICC scores indicating excellent reliability of visual synchronization measurements, suggesting that one measurement would be sufficient. Most athletes had similar scores before and after practice, indicating little change in visual performance following exercise. EYE-SYNC® goggles have the potential for use in obtaining objective visual performance measures of ocular-motor function for sideline assessment of concussion and return to play decisions.